(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2019)
Nurses are among the professionals who wish to pursue their graduate studies and dream of better working conditions. If nurses interested in continuing their study can be attracted to higher positions and given the chance to obtain a graduate degree, this will be beneficial to the higher education system, nursing administration, and the nursing profession as a whole. Their meaningful accounts are worth sharing. This study utilized the qualitative method of research specifically the Husserlian type of Phenomenology. The participants of the study were ten clinical nurses of the Province of La Union. Moreover, purposive sampling was used. An in-depth interview was done. An unstructured questionnaire was utilized in this study. Cool and Warm Analysis -Moustakas in Creswell method of interpretation are used in analyzing the data. There are Seven (7) Themes emerged in this study. The theme I: "Delightful Dilemmas" talks on the Participants’ Doubts and Fears before Enrolling to Graduate Studies. Theme II: "Sky is the Limit" is The Participants’ Motivations for Enrolling in their Graduate Studies. Theme III: "The Uphill Climb" is the Challenges Encountered by the Participants. This phase of their journey towards finishing their graduate studies where they have to deal with various challenges. Theme IV: "Staying Tough while the Going Gets Tough" is how the Participants Cope despite the overlapping challenges encountered while they are enrolled in their graduate studies. Theme V: "The Perks of Being a Graduate Student" are the benefits of Being Enrolled in the Graduate School. They can see the benefits or the advantages of pursuing their graduate study. Theme VI: "Wishing Upon a Star" are the Participants’ Desires to Help Improve their Plight. This showed the participants’ desires to help improve their plight not only as student-nurses but also as a clinical nurse in general. Theme VII: "Keeping the Grit" the Participants’ are determined to Finish their Studies. They are determined to run the race no matter how bumpy the roads. From the participants’ verbalizations of experiences the study found the following: 1) their dilemmas before their enrolment at the graduate school, 2) their motivations, 3) the challenges they encountered, 4) how they coped with the challenges, 5) the benefits they get from being enrolled, 6) their desires for the betterment of the status of nurses in general, and (7) their determination to finish their graduate studies.